Prevalence and Nutritional Status of Infants With Cystic Fibrosis and Pseudo-Bartter Syndrome During the First Year of Life. (December 2014) - Del Ciampo, Ieda Regina Lopes; Martins, Natalia; Sawamura, Regina; Facincani, Inalda; Del Ciampo, Luiz Antonio; Fernandes, Maria Inez Machado
Background. Cystic fibrosis (CF) is an autosomal recessive disease more commonly occurring among Caucasians. An electrolyte derangement, pseudo-Bartter syndrome (PBS) is a complication leading to failure to thrive. Objectives. To describe the prevalence of PBS and related nutritional status in infants with CF detected after a newborn screening test who were treated in a Brazilian town with a very warm climate. Methods. This was a retrospective study with data collected from medical records. The diagnosis of PBS was based on hypokalemia (K + < 3.5 mEq/L), hyponatremia (Na ++ < 135 mEq/L), low urinary sodium (Na ++ < 20 mEq/L), and metabolic alkalosis (pH > 7.45; bicarbonate >28 mEq/L). The anthropometric data assessed were weight and length at the following: birth, diagnosis of CF, diagnosis of PBS, and discharge from hospital after correction of PBS and at 12 months of age. The nutritional indicators were weight/height, weight/age, length/age, and body mass index/age ratios. The cutoff point was z-score < p −2 (World Health Organization reference). Data were analyzed using the Anthro (World Health Organization) and Epi-info 2007 programs. Results. Twelve infants with CF were included, and 41.6% (5) had PBS. There was progressive improvement of nutritional status after CF management and after an early diagnosis and management of PBS. Conclusions. The prevalence of PBS was high. There were mild clinical manifestations of PBS accompanied by compromised nutritional status, identified in patients from a region of hot weather.